Post-polio eradication: vaccination strategies and options for India - Jayakrishnan Thayyil; Thejus Jayakrishnan (PAGEPress Publications, 2014)
In 1988, the World Health Organization (WHO) resolved to eradicate poliomyelitis globally. Since then, the initiative has reported dramatic progress in decreasing the incidence of poliomyelitis and limiting the geographical extent of transmission. 2013 is recorded as the second consecutive year not reporting wild poliovirus (WPV) from India. If the country can retain this position for one more year India will be declared as polio eradicated. What should be the future vaccination strategies? We searched and reviewed the full text of the available published literature on polio eradication via PubMed and examined Internet sources and websites of major international health agencies. The oral polio vaccine (OPV) has been the main tool in the polio eradication program. Once WPV transmission is interrupted, the poliomyelitis will be caused only by OPV. India could expect 1 vaccine-associated paralytic polio per 4.2-4.6 million doses of OPV. Considering the threat of vaccine-derived viruses to polio eradication, WHO urged to develop a strategy to safely discontinue OPV after certification. The ultimate aim is to stop OPV safely and effectively, and eventually substitute with inactivated polio vaccine (IPV). The argument against the use of IPV is its cost. From India, field based data were available on the efficacy of IPV, which was better than OPV. IPV given intradermally resulted in seroconversion rates similar to full-dose intramuscular vaccine. The incremental cost of adopting IPV to replace OPV is relatively low, about US $1 per child per year, and most countries should be able to afford this additional cost.